Increasing the Frequency of Posbindu Implementation for FK-KMK UGM Students as Support for Accelerating HPU UGM - Lainatus Shifa, Hilda Fauziah (BKM Public Health and Community Medicine, 2024)
Purpose: Research on the health conditions of the academic community at UGM indicates that approximately 33.2% of UGM students have poor nutritional status. Additionally, some students who are about to intern and UGM alumni applying for jobs do not meet the health test requirements. The Posbindu program is already implemented through HPU FK-KMK UGM, but it is not routinely conducted for students. Therefore, advocacy for the policy to regularly implement Posbindu for FK-KMK UGM students is necessary as a preventive measure for modifiable non-communicable disease (NCD) risk factors and to accelerate the HPU UGM initiative promoting a healthy campus. This paper aims to outline the advocacy steps for increasing the frequency of regular Posbindu implementation for FK-KMK UGM students. Methods: Non-communicable diseases are a major health issue that increases annually and contributes significantly to global mortality. The 2018 Basic Health Research (Riskesdas) in Indonesia shows that NCD incidence tends to rise from the age of 15-18, suggesting early control is essential. Posbindu is a community-based health effort (UKBM) aimed at early detection, monitoring, and follow-up of NCD risk factors. UGM declared itself a Health Promoting University in July 2019. The HPU FK-KMK UGM runs the "Posbindu Sehati" for faculty, staff, and students. However, the Posbindu for students is not conducted monthly. Advocacy steps include formal and informal collaborations with BEM FK-KMK UGM, HPU FK-KMK UGM Brand Ambassadors, and the HPU FK-KMK UGM team. These stakeholders will then formally advocate to the FK-KMK UGM Dean to consider and issue a policy to increase the frequency of Posbindu implementation for FK-KMK UGM students. Results: The advocacy process is expected to lead to routine Posbindu sessions, improving student health by early detection and management of NCD risk factors. Conclusion: Regular implementation of Posbindu can significantly enhance student health and align with UGM's Health Promoting University goals.